Legionnaires’ disease: A review of emerging public health threats - Aswin Rafif Khairullah; Harimurti Nuradji; Diana Nurjanah; Ni Luh Putu Indi Dharmayanti; Bantari Wisynu Kusuma Wardhani; Syahputra Wibowo; Ikechukwu Benjamin Moses; Dea Anita Ariani Kurniasih; Ima Fauziah; Muhammad Khaliim Jati Kusala; Kartika Afrida Fauzia (International Journal of One Health)
Background and Aim: Legionnaires’ disease (LD), caused by the Gram-negative bacterium Legionella pneumophila, has emerged as a significant public health concern due to its rising incidence and high morbidity and mortality rates. This review comprehensively examines the etiology, epidemiology, pathogenesis, clinical presentation, diagnosis, treatment, and prevention of LD. The bacterium thrives in aquatic environments, often within biofilms and protozoan hosts, contributing to its resilience and widespread distribution in natural and man-made water systems. Transmission primarily occurs through the inhalation of contaminated aerosols, with immunocompromised individuals, the elderly, and smokers being at heightened risk. Clinically, LD presents as a severe pneumonia with systemic involvement, and its diagnosis often relies on culture, urinary antigen tests, and molecular methods. The treatment landscape is dominated by macrolides and fluoroquinolones, with emerging research into alternative therapies to combat antimicrobial resistance. Effective public health strategies, including rigorous water management practices and infection control measures, are vital in mitigating the risk of outbreaks. This review aims to enhance clinical awareness and inform public health initiatives by elucidating the complex interplay between bacterial virulence, host factors, and environmental conditions that contribute to LD transmission and persistence. A better understanding of these dynamics is crucial for developing robust prevention and control strategies, ultimately reducing the global burden of this potentially life-threatening disease.